1985
DOI: 10.1159/000124189
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Monoaminergic Activity and Pituitary Function in Male Rats with Estrogen-Induced Pituitary Hyperplasia

Abstract: The mechanism by which estrogen enhances prolactin (PRL) secretion and induces hyperplasia of lactotrophs is not defined clearly. The objective of this study was to examine hypothalamic monoaminergic PRL regulatory systems and pituitary hormone secretion in the early and later stages of estrogen-induced hyperprolactinemia and pituitary hyperplasia. Dopamine (DA) and serotonin (5-HT) turnover were determined in microdissected brain regions 3 and 30 days after a single subcutaneous dose of estradiol (2 mg) to ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
4
11
0
Order By: Relevance
“…This result is in agreement with previous studies that estrogen stimulates PRL release, both in vivo [Terry et al, 1985] and in vitro [Ben-David et al, 1964;Nicoll and Meites, 1964]. The role of PRL in adrenal function and steroid hormone secretion has been studied.…”
Section: Discussionsupporting
confidence: 92%
“…This result is in agreement with previous studies that estrogen stimulates PRL release, both in vivo [Terry et al, 1985] and in vitro [Ben-David et al, 1964;Nicoll and Meites, 1964]. The role of PRL in adrenal function and steroid hormone secretion has been studied.…”
Section: Discussionsupporting
confidence: 92%
“…We confirmed that in vivo treatment with EB in Ovx rats resulted in a dose-dependent increase the secretion of plasma PRL compared to oiltreated Ovx rats. This is consistent with the observation that acute and chronic effects of E 2 on male rats yield a significant increase in plasma PRL and pituitary PRL [Terry et al, 1985]. However, these results indicate that there is positive correlation between plasma PRL and corticosterone under the influence of E 2 .…”
Section: Discussionsupporting
confidence: 92%
“…It has been well-established that the effects of estrogen on plasma and pituitary PRL could be a direct action of estrogen on pituitary lactotrophs [Terry et al, 1985] or due to indirect effects of estrogen on hypothalamic PRL regulatory systems, i.e., inhibition of dopamine release [Casanueva et al, 1982] or stimulation of serotonin [Nakagawa et al, 1980]. We confirmed that in vivo treatment with EB in Ovx rats resulted in a dose-dependent increase the secretion of plasma PRL compared to oiltreated Ovx rats.…”
Section: Discussionsupporting
confidence: 76%
“…In a recent study, which examined the activity of dopamine neurones during the development of adenoma formation, it was shown that dopamine neurones continue to function actively even while oestrogen levels are high (Terry, Craig, Hughes et al 1984). The purpose of the present study was to charac¬ terize prolactin regulation during the acute develop¬ ment of oestrogen-induced pituitary hyperplasia with a pharmacological approach, testing for potential pituitary and hypothalamic disturbances.…”
Section: Introductionmentioning
confidence: 93%